Relationship Between Family Support and Activity in the Elderly Joining the Posyandu for Elderly Literature StudiesRelationship Between Family Support and Activity in the Elderly Joining the Posyandu for Elderly Literature Studies - Nur Saibah Herniati; Joko Pitoyo; Sih Ageng Lumadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2022)
ABSTRACT Background: The proportion of the activity level of the elderly who participate in posyandu activities is still low, and the presence of the elderly is far from the goal. One of the efforts to overcome this problem is family support. This study aims to determine the relationship between family support and the participation of the elderly in posyandu activities for the elderly. Aim: This study aims to determine whether family support has a relationship with the wisdom of the elderly in attending the posyandu for the elderly. Method: The author uses a literature study method with literature using three data bases ProQuest, Pubmed, and Google scholar. 10 articles were obtained based on inclusion and exclusion criteria. For previous research, mix study methods, cross-sectional, correlation, and descriptive were published from 2015-2020. This literature is reviewed based on year of publication, title, abstract, full text and methodology assessed for appropriate study. Then the data tabulation and narrative analysis were carried out. Results: There were 10 articles based on the inclusion and exclusion criteria. Studies include those relating to the relationship between family support and the activity of the elderly in attending the posyandu for the elderly. (n=10). Conclusion: The relationship of family support is very influential in increasing the activity of the elderly to participate in the posyandu for the elderly. For this reason, families are advised to extend their support to the elderly so that the elderly can participate more actively in Poshand. Posyando activities and improving the quality of health services for the elderly. Keywords: Family Support, , Posyandu, Elderly,health, activeness